Age-dependent increase of perineuronal nets in the human hippocampus and precocious aging in epilepsy - Lehner, Annika; Hoffmann, Lucas; Rampp, Stefan; Coras, Roland; Paulsen, Friedrich; Frischknecht, Renato; Hamer, Hajo; Walther, Katrin; Brandner, Sebastian; Hofer, Wiebke; Pieper, Tom; Reisch, Lea Marie; et al. (Epilepsia Open, 2024)
Objective: Perineuronal nets (PNN) are specialized extracellular matrix (ECM) components of the central nervous system, frequently accumulating at the surface of inhibitory GABAergic interneurons. While an altered distribution of PNN has been observed in neurological disorders including Alzheimer's disease, schizophrenia and epilepsy, their anatomical distribution also changes during physiological brain maturation and aging. Such an age-dependent shift was experimentally associated also with hippocampal engram formation during brain maturation. Our aim was to histopathologically assess PNN in the hippocampus of adult and pediatric patients with temporal lobe epilepsy (TLE) compared to age-matched post-mortem control subjects and to compare PNN-related changes with memory impairment observed in our patient cohort. Methods: Sixty-six formalin-fixed and paraffin-embedded tissue specimens of the human hippocampus were retrieved from the European Epilepsy Brain Bank. Twenty-nine patients had histopathologically confirmed hippocampal sclerosis (HS), and eleven patients suffered from TLE without HS. PNN were immunohistochemically visualized using an antibody directed against aggrecan and manually counted from hippocampus subfields and the subiculum. Results: PNN density increased with age in both human controls and TLE patients. However, their density was significantly higher in all HS patients compared to age-matched controls. Intriguingly, TLE patients presented presurgically with better memory when their hippocampal PNN density was higher (p < 0.05). Significance: Our results were compatible with age-dependent ECM specialization in the human hippocampus and its precocious aging in the epileptic condition. These observations confirm recent experimental animal models and also support the notion that PNN play a role in memory formation in the human brain. Plain Language Summary: “Perineuronal nets” (PNN) are a specialized compartment of the extracellular matrix (ECM), especially surrounding highly active neurons of the mammalian brain. There is evidence that PNN play a role in memory formation, brain maturation, and in some pathologies like Alzheimer's disease, schizophrenia or epilepsy. In this study, we investigated the role of PNN in patients suffering from drug-resistant focal epilepsy compared to controls. We found that with increasing age, more neurons are surrounded by PNN. Similarly, all epilepsy patients but especially patients with better memory performance also had more PNN. This study raises further interest in studying ECM molecules in the human brain under physiological and pathophysiological conditions.
CRIS-Team Scopus Importer:2024-06-21
Keywords: brain; extracellular matrix; hippocampal sclerosis; maturation; neuropathology